Toward a Consensus in the Repertoire of Hemocytes Identified in Drosophila - Cattenoz, Pierre B.; Monticelli, Sara; Pavlidaki, Alexia; Giangrande, Angela (Frontiers in Cell and Developmental Biology, 2021)
The catalogue of the Drosophila immune cells was until recently limited to three major cell types, based on morphology, function and few molecular markers. Three recent single cell studies highlight the presence of several subgroups, revealing a large diversity in the molecular signature of the larval immune cells. Since these studies rely on somewhat different experimental and analytical approaches, we here compare the datasets and identify eight common, robust subgroups associated to distinct functions such as proliferation, immune response, phagocytosis or secretion. Similar comparative analyses with datasets from different stages and tissues disclose the presence of larval immune cells resembling embryonic hemocyte progenitors and the expression of specific properties in larval immune cells associated with peripheral tissues